2022
DOI: 10.1093/jac/dkac182
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic modelling of caspofungin to develop an extended dosing regimen in paediatric patients

Abstract: Background Echinocandins are commonly used in treatment and prophylaxis of invasive fungal diseases. Intravenous daily dosing for prophylaxis in the outpatient setting can however become a hurdle for adequate compliance in the paediatric population. Objectives Simulations were performed to assess extended twice-weekly dosing for antifungal prophylaxis using caspofungin. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The modeling strategies and final PK parameters of the included studies are summarized in Table 2 . Ten studies [ 11 , 12 , 23 , 27 , 28 , 29 , 30 , 32 , 33 , 34 ] used NONMEM software, with first-order conditional estimation with interaction (FOCE-i) being the most used algorithm [ 11 , 12 , 23 , 27 , 28 , 32 , 33 , 34 ]. Most studies employed a two-compartment model to describe caspofungin PKs, although two studies [ 25 , 34 ] utilized a one-compartment model due to sparse sampling schedules that may not accurately represent the characteristics of a two-compartment PK model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The modeling strategies and final PK parameters of the included studies are summarized in Table 2 . Ten studies [ 11 , 12 , 23 , 27 , 28 , 29 , 30 , 32 , 33 , 34 ] used NONMEM software, with first-order conditional estimation with interaction (FOCE-i) being the most used algorithm [ 11 , 12 , 23 , 27 , 28 , 32 , 33 , 34 ]. Most studies employed a two-compartment model to describe caspofungin PKs, although two studies [ 25 , 34 ] utilized a one-compartment model due to sparse sampling schedules that may not accurately represent the characteristics of a two-compartment PK model.…”
Section: Resultsmentioning
confidence: 99%
“…All studies incorporated between-subject variability (BSV), with a median of 27.5% (range: 11.8–42.3%) in CL across the 13 studies. Residual unexplained variability was described by proportional [ 11 , 23 , 25 , 26 , 27 , 28 , 31 , 32 , 33 , 34 ], additive [ 12 , 30 ], or combined models [ 29 ]. Proportional errors with coefficients of variation ranged from 12.2% to 36% in eleven studies, while three studies [ 12 , 29 , 30 ] included addictive errors ranging from 0.0941 to 0.73 mg/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, raw data from children aged 3 months to gillosis exist, the proposed regimen also would cover the PK/PD targets proposed for the treatment of invasive candidiasis. 39 Taken together, these studies provide a sound pharmacokinetic and pharmacodynamics rationale for extended dosing regimens of caspofungin and micafungin and their further study in preferentially large and controlled clinical trials.…”
Section: Extended Dosing Regimens Of Echinocandinsmentioning
confidence: 92%
“…Monte Carlo simulations revealed that a 200 mg/m 2 twice‐weekly extended dosing regimen, with a maximum total dose of 200 mg should result in average weekly exposures that match those obtained following the approved once‐daily dosing. While no accepted PK/PD targets for invasive aspergillosis exist, the proposed regimen also would cover the PK/PD targets proposed for the treatment of invasive candidiasis 39 …”
Section: New Data On Alternative Dosing Regimensmentioning
confidence: 99%